KOMUNIKASI ANTARPRIBADI DAN KETERBUKAAN DIRI REMAJA TERHADAP TEMAN SEBAYA DIKALANGAN SISWA HOMESCHOOLING - Saesar Deka Al Ramadhan (2023)
This study focuses on personal communication and youth self-awareness among homeschooling students. This study aims to understand how a teenager performs personal communication and self-openness, especially homeschooling students. The method used in this study is a qualitative approach using phenomenological approaches. In this study the data collection techniques to be used are interview techniques with six students from three different homeschooling and also observations analyzed and presented in descriptive form. Research results show that sources tend to have an open attitude and to conduct self - openness behavior only to trustworthy people. This is due to the comfort and trust to channel his feelings without fear of being judged. KeyWord: Personal Communication, Self Disclosure, Teenager, Homeschooling.